Impak perubahan guna tanah di Changlun terhadap masyarakat setempat - Mariyappan, Raman (2000)
Land use changes occur due to many factors.One of the most important factor is government policy regarding rural infrastructure developments.This paper highligts the impact being noticed when such policy was implemented.The degree of impact depends how far the local population participate actively in such developments.